Baseline Mental Health Status and Early Psychiatric Outcomes after Metabolic-Bariatric Surgery: A Retrospective Cohort Study - Patricia M. Ortega; Luke Boyle; Dana Mahdi; Zahra Al-Essah; Ali Abdul Hussein; Mina Abdul Hussein; Aslesha Deshraju; Elena Brachimi; Prasidha Rai; Elsie Ampomah; Neha Hussain; Faizan Kiani; et al. (Obesity Surgery, 2026)
Abstract Objective To evaluate whether documented preoperative mental health (MH) conditions were associated with early postoperative psychiatric events and metabolic outcomes after primary metabolic-bariatric surgery (MBS). Methods A retrospective cohort study of adults who underwent primary MBS at a tertiary UK bariatric centre between April 2021 and March 2024 was conducted. Preoperative MH conditions and postoperative outcomes were identified via review of electronic health records. Comparisons between groups were analysed using Fisher’s exact test and regression models adjusted for age, sex, preoperative BMI, and surgery type. Results Among 482 patients, 217 (45.0%) had at least one documented preoperative MH condition. During 2-year follow-up, suicidal ideation was recorded in 6/217 (2.8%) in the MH group versus 1/265 (0.4%) in the non-MH group and self-harm (including suicide attempt) in 5/217 (2.3%) versus 1/265 (0.4%), respectively. Preoperative MH conditions were associated with higher odds of postoperative suicidal ideation (OR 6.75, 95% CI 1.09–41.86; p = 0.0420), while the association with self-harm was directionally similar but not statistically significant (OR 5.10, 95% CI 0.80–32.72; p = 0.0860). Weight-loss and metabolic outcomes did not differ materially by baseline MH status. Conclusions In this single-centre cohort, patients with documented preoperative MH conditions achieved comparable metabolic benefit after surgery but had higher recorded early suicidality-related events. Although causality cannot be inferred, these findings support structured postoperative MH follow-up.